2017
DOI: 10.1080/10428194.2017.1365854
|View full text |Cite
|
Sign up to set email alerts
|

Real life experience with frontline azacitidine in a large series of older adults with acute myeloid leukemia stratified by MRC/LRF score: results from the expanded international E-ALMA series (E-ALMA+)

Abstract: Azacitidine (AZA) prolonged overall survival (OS) in the AZA-AML-001 trial. However, few subjects were randomized to AZA or intensive chemotherapy (IC). The Medical Research Council (MRC) and the Leukemia Research Foundation (LRF) developed a score for older AML patients receiving IC or non-intensive regimens, whereas the E-ALMA study validated a score for survival and response in elderly patients receiving AZA in daily practice. Both identified three groups with different risk estimates. This analysis evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 34 publications
8
17
0
Order By: Relevance
“…30 Gupta et al found no association between WBC at diagnosis and survival, while two European studies of 710 and 149 patients treated with frontline azacitidine reported an increased mortality (with HR of 1.52 and 2.38, respectively) in subjects with high WBC. [26][27][28] Our data thus add to the body of evidence supporting an unfavourable role of elevated WBC level (HR=1.12; 95% CI: 1.06-1.18).…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…30 Gupta et al found no association between WBC at diagnosis and survival, while two European studies of 710 and 149 patients treated with frontline azacitidine reported an increased mortality (with HR of 1.52 and 2.38, respectively) in subjects with high WBC. [26][27][28] Our data thus add to the body of evidence supporting an unfavourable role of elevated WBC level (HR=1.12; 95% CI: 1.06-1.18).…”
Section: Discussionsupporting
confidence: 60%
“…Genetic abnormalities are recognized key factors in the prognosis of AML . Some studies examining predictors of survival in patients treated with epigenetic therapy confirmed that cytogenetics play an important role in these patients, too, though others did not confirm this finding …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondary acute myeloid leukemia (sAML) evolving from an antecedent hematological disorder and therapy‐related sAML represent high‐risk subsets of AML and are associated with poor clinical outcome . The hypomethylating agents (HMA), azacitidine, and decitabine represent treatment options for elderly AML patients including sAML patients unfit for intensive chemotherapy . Treatment options after HMA failure usually consist of BSC or low‐dose cytarabine, and the prognosis remains limited with a median OS of 3.4 months .…”
Section: Introductionmentioning
confidence: 99%
“…1 The hypomethylating agents (HMA), azacitidine, and decitabine represent treatment options for elderly AML patients including sAML patients unfit for intensive chemotherapy. [2][3][4][5] Treatment options after HMA failure usually consist of BSC or lowdose cytarabine, and the prognosis remains limited with a median OS of 3.4 months. 6 Therefore, there is a high clinical demand for new therapeutic targets.…”
Section: Introductionmentioning
confidence: 99%